Dystocia due to Unilateral Uterine Torsion with Concurrent Uterine Rupture in a Rottweiler Bitch - Das, Jayanta; Sachan, Nikhil; Kumar, Rajesh; Saurabh (The Indian Journal of Animal Reproduction, 2025)
A 3-year-old pregnant Rottweiler bitch was presented with a primary complaint of bloody genital discharge and loss of  appetite past two days. History revealed bitch was presented 63 days post-mating, expected to whelp within the next 48  hours and treated with oxytocin. Physical examination revealed a partially dilated cervix with the notable palpation of  the foetal head. A caesarean section was performed to resolve the case. The bitch was recovered uneventfully.
Keywords: Bitch; Uterine rupture; Uterine torsion